2012
DOI: 10.1029/2012gc004304
|View full text |Cite
|
Sign up to set email alerts
|

Controls of faulting and reaction kinetics on serpentinization and double Benioff zones

Abstract: [1] The subduction of partially serpentinized oceanic mantle may potentially be the key geologic process leading to the regassing of Earth's mantle and also has important consequences for subduction zone processes such as element cycling, slab deformation, and intermediate-depth seismicity. However, little is known about the quantity of water that is retained in the slab during mantle serpentinization and the pattern of serpentinization that may occur during bending-related faulting; an initial state that is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 92 publications
1
46
0
Order By: Relevance
“…If this mechanism actually operates in the mantle, it could explain the formation of double seismic zones. Iyer et al (2012) suggested that the double hydrated zone at the depths of the slab mantle, through slab unbending ( Fig. 22; Faccenda et al 2012) and maximum serpentinization at c. 270°C, may together cause the variations in the observed separation of the double seismic zone.…”
Section: Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…If this mechanism actually operates in the mantle, it could explain the formation of double seismic zones. Iyer et al (2012) suggested that the double hydrated zone at the depths of the slab mantle, through slab unbending ( Fig. 22; Faccenda et al 2012) and maximum serpentinization at c. 270°C, may together cause the variations in the observed separation of the double seismic zone.…”
Section: Reviewmentioning
confidence: 95%
“…The possibility of deep hydration of the slab mantle prior to subduction was also demonstrated by a recent 2-D reactive-flow model simulation of hydration processes at the trench-outer rise region (Iyer et al 2012). Iyer et al (2012) developed a reaction-transport model that enables better quantification of the amount and depth at which hydration occurs in an incoming oceanic plate due to normal faulting caused by the bending force. The hydration patterns determined with this model show the formation of a highly serpentinized band in the slab mantle centered at the 270°C isotherm.…”
Section: Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Oceanic peridotites acquire H 2 O during serpentinization (up to~13%), together with significant amounts of B and Cl; their subduction may carry part of this boron-enriched water back into the mantle (Barnes and Sharp, 2006;Bonatti et al, 1984;Boschi et al, 2008;Iyer et al, 2012;Kodolányi et al, 2012;Rüpke et al, 2004;Scambelluri et al, 2004a,b;Ulmer and Trommsdorff, 1995;Vils et al, 2009). Low-T ultramafic rock-seawater reactions can release Mg to the ocean (Niu, 2004;Snow and Dick, 1995), deposit carbonates (Bonatti et al, 1980) and uptake organic carbon (Delacour et al, 2008;Früh-Green et al, 2003) that can also be recycled later through subduction (Kerrick and Connolly, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…We use equation to determine the reaction extent at any time but modify it to include a linear dependence on porosity to mimic the effect of water supply on the reaction rate (e.g., Iyer et al, ), so that trueα̇=Kαϕfalse(1αfalse)2. To describe creep in the product gypsum phase we make use of the work of de Meer (), who found that the bulk strain rate due to uniaxial creep of wet gypsum can be described by an equation of the form trueε̇=Aσa2d2.5ε3, where A is a constant equal to 4 × 10 −33 and d is the grain size in meters. Equation gives the strain rate due to compaction via decrease in the pore volume.…”
Section: Discussionmentioning
confidence: 99%